Massive Pulmonary Haemorrhage As A Complication Of Intrapleural Streptokinase Therapy - Adilah W Ab Rahim; Lau Chiew Yee; Aliyyah Mohammad Khuzaini (Galenos Publishing House, 2024)
Indexed by WOS/ Scopus